Optimizing Early Detection: Key Factors Influencing Hospital Early Warning System Implementation – A Systematic Review - Hilma Fitria Nur Faiz; Masyitoh Basabih (GLOBAL HEALTH SCIENCE GROUP, 2026)
Early Warning System (EWS) is a clinical tool used to detect early signs of patient deterioration and prevent delayed interventions. Despite broad implementation, challenges persist related to healthcare providers’ readiness, organizational support, system design, and varied care environments. This study aims to identify and analyze factors influencing EWS implementation based on recent empirical evidence to support more effective and sustainable use in healthcare settings. A systematic review was conducted using five electronic databases: PubMed, Scopus, ScienceDirect, SpringerLink and ProQuest. The search employed key terms including “Early Warning System,” “EWS score,” “National Early Warning Score,” “NEWS2,” “hospital,” “implementation,” “adherence,” “barriers,” “facilitators,” and “healthcare professionals.” A total of 1,163 articles were initially identified. Following duplicate removal, title and abstract screening, and full-text assessment in accordance with PRISMA guidelines, 23 peer-reviewed articles met the inclusion criteria. Eligible studies were open-access, published in English between 2018 and 2025, and reported original empirical findings related to EWS implementation. This review was registered with PROSPERO. The included studies identified four major categories of factors influencing EWS implementation: (1) Individual factors, including clinical experience, attitudes, knowledge, and emotional readiness; (2) Organizational factors, such as managerial support, patient safety culture, infrastructure, and institutional policies; (3) Intervention-related factors, including system design, training quality, and integration with information technology; and (4) Environmental factors, encompassing resource availability, facility conditions, and the need for local adaptation. Successful implementation of Early Warning Systems requires a comprehensive and integrated approach. Effectiveness and long-term sustainability are influenced by the extent to which implementation strategies are aligned with local clinical contexts, supported by structured training programs, embedded within a strong patient safety culture, and reinforced through multidisciplinary collaboration.